PERANCANGAN APLIKASI SISTEM INFORMASI LOWONGAN PEKERJAAN SEBAGAI MEDIA PARTNER BERBASIS WEB DAN MOBILE - Nitu, Fulgensius Nemesio Manfret; Sejati, RR. Hajar Puji (J-Icon : Jurnal Komputer dan Informatika, 2024)
The increasing number of job seekers in Indonesia has made job vacancy information applications the most accessed application among job seekers, especially for students graduating from vocational schools. Vocational High Schools (SMK) are believed to be schools that are prepared to produce workers who have the skills and expertise needed in the world of work. However, most of the existing job vacancy applications are very limited in presenting information on job vacancies that match the expertise and experience of alumni and even students of SMK Ma’arif 1 Yogyakarta. For this reason, in helping graduates of SMK Ma’arif 1 Yogyakarta, a forum is needed that can facilitate these graduates in obtaining information on job vacancies that are by the skills and location of the alumni’s residence area. The purpose of this project is to develop a system that will assist students at SMK Ma’arif 1 Yogyakarta in locating information about employment openings. This job vacancy application was created using the prototype method because it is very suitable for building Android-based job vacancy information system software. The system design made by the author was successfully implemented into a mobile application using the Kotlin coding language and Android Studio. Based on testing, the application built can change the information system that was originally delivered manually into an electronic system by developing mobile applications so that there is interaction between system developers and application users that can be used to get job vacancy information easily.